1958
DOI: 10.1021/ac60133a018
|View full text |Cite
|
Sign up to set email alerts
|

Coulometric Titrations with Mercury(I and II). Determination of Cyanide

Abstract: sition a t lower p H levels, with complete breakdown resulting from refluxing with mineral acid.Aliquots of the various solutions were tested for their content of free isonicotinic acid, the breakdown product, using essentially the method of Rubin and associates (4) based on the bromocyanogen reaction of Mueller and Fox ( 3 ) . With decreasing assay values for iproniazid, concomitantly increasing quantities of isonicotinic acid were found.Other aliquots of the solutions refluxed for 10 hours were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
1973
1973

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the coulometric titration of cyanide, Przybylowicz and Rogers (97) found that the results with electrolytically generated mercury(II) were slightly superior to those with silver(I) generated under the same conditions.…”
Section: Apparatus and Methodologymentioning
confidence: 99%
“…In the coulometric titration of cyanide, Przybylowicz and Rogers (97) found that the results with electrolytically generated mercury(II) were slightly superior to those with silver(I) generated under the same conditions.…”
Section: Apparatus and Methodologymentioning
confidence: 99%
“…Primary amines interfere in the latter determination, but these can be removed by reaction with salicylaldehyde; tertiary amines do not interfere. Mercuric ion was reported to be slightly superior to silver ion for the titration of cyanide (118). Microgram amounts of sulfide could be titrated with errors of the order of ±0.2% (119).…”
Section: Currentmentioning
confidence: 99%